Struktur modal Sebagai Faktor Mediasi: Studi Empiris pada Perusahaan-Perusahaan Sub-Sektor Farmasi yang Listing di Bursa Efek Indonesia Periode 2012-2022 - Rosliana Marten; Akhmadi Akhmadi (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to empirically test the influence of profitability and liquidity on company value with capital structure as an intervening variable. Using 6 company samples from 11 companies in the Pharmaceutical Sub-Sector listed on the Indonesian Stock Exchange. The research sample was determined using a purposive sampling technique. The observation period is 2012-2021, so the research used 60 observational data. Data analysis in this study used descriptive statistics, multivariate linear regression, and hypothesis testing. The research results prove that liquidity has a positive and significant effect on company value. Liquidity has a negative and significant effect on capital structure. However, capital structure cannot mediate the effect of liquidity on company value.